Integration of wearable sensors into sensory room therapies for children with developmental challenges - Movazzaf Gharehbagh, Bita (My University, 2025)
Wearable sensor technologies are becoming powerful tools in healthcare and therapy, especially for children with disabilities such as autism or sensory processing disorders. These devices can track a person’s heart rate, body temperature, movement, stress level, and even their location. When used in sensory rooms, special spaces designed to help children feel calm or focused, wearable sensors can make the therapy more personal and effective. For example, if a child is feeling stressed, the room’s lights, music, or activities can adjust automatically to help the child feel better. This creates a smart, interactive space where therapy responds to the child’s real needs in real time. This report explores how wearable sensors can improve sensory room therapy by offering three key benefits: tracking where the child is in the room, monitoring their physical and emotional responses, and recording behavior for long-term review. Examples include a spinning toy with sensors for children who show repetitive behaviors, and GPS-based systems that track which therapy zones a child visits most. These technologies help therapists understand what works best for each child and plan better therapy sessions. The goal is to make therapy more responsive, safe, and tailored to the needs of each child.
Keywords: Wearable sensor; Sensory room